2020
DOI: 10.1111/pin.13047
|View full text |Cite
|
Sign up to set email alerts
|

Combined A20 and tripartite motif‐containing 44 as poor prognostic factors for breast cancer patients of the Japanese population

Abstract: We previously reported that a strong immunoreactivity of tripartite motif‐containing 44 (TRIM44) predicts the poor prognosis of patients with invasive breast cancer, and proposed that TRIM44 activates nuclear factor‐κB (NF‐κB) signaling as a causative mechanism. In the present study, we examined the clinicopathological roles of A20, which is known to be an NF‐κB responsive gene, with TRIM44, in an updated cohort. Tissue samples of invasive breast cancer were obtained from 140 Japanese female breast cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Tripartite motif containing 44 (TRIM44), an important member of the TRIM family, contributes to a variety of pathological states and is closely associated with malignant tumor etiology and progression (Chen et al 2021a;Liu et al 2019;Sato et al 2021). In addition, TRIM44 gene knockout inhibits PCa cell proliferation and invasion (Tan et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Tripartite motif containing 44 (TRIM44), an important member of the TRIM family, contributes to a variety of pathological states and is closely associated with malignant tumor etiology and progression (Chen et al 2021a;Liu et al 2019;Sato et al 2021). In addition, TRIM44 gene knockout inhibits PCa cell proliferation and invasion (Tan et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that dysregulation of TRIM44 protein is associated with several diseases. TRIM44 promotes cell proliferation and metastasis in various carcinogeneses, such as renal cell carcinoma, breast cancer and melanoma ( Yamada et al, 2020 ; Kashimoto et al, 2012 ; Xiong et al, 2018 ; Ji et al, 2020 ; Zhou et al, 2017 ; Yamada et al, 2017 ; Kawabata et al, 2017 ; Tan et al, 2017 ; Zhou et al, 2019 ; Li et al, 2019 ), and also shows promise as a potential prognostic predictor and a therapeutic target for patients with multiple tumors ( Ong et al, 2013 ; Kawaguchi et al, 2017 ; Li et al, 2021 ; Lyu et al, 2021 ; Peters et al, 2010 ; Ong et al, 2014 ; Chen et al, 2021 ; Liu et al, 2019 ; Robins et al, 2014 ; Sato et al, 2021 ). In addition, TRIM44 has also been reported to participate in neuron differentiation, neuron maturation ( Kashevarova et al, 2014 ) and aniridia ( Zhang et al, 2015a ; Samant et al, 2016 ; Lim et al, 2017 ; Landsend et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The staining proportion was measured as the percentage of stained tumor cells. Immunoreactivity (IR) of TRIM39 was defined as “positive” when the nucleus of more than 10% of tumor cells were stained as moderate and strong 13 . Ki67 labeling index (LI) was evaluated using e‐Count2 cell counting software (e‐Path) 22 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, we previously showed that TRIM25/estrogen‐responsive finger protein (Efp) plays a tumor‐promoting role in breast cancer by functioning as an E3 ubiquitin ligase that degrades the cell cycle checkpoint protein 14‐3‐3 sigma 8 and possibly by stabilizing and activating retinoic acid inducible gene‐I, a molecule originally shown to regulate innate immunity 9–11 . We also demonstrated that TRIM44 plays a role in the progression of breast cancer by promoting cell proliferation and migration with enhanced nuclear factor‐κB (NF‐κB) signaling 12,13 …”
Section: Introductionmentioning
confidence: 99%